Attachment and adaptation to breast cancer: The mediating role of avoidant emotion processes - Brandão, Tânia (2018)
Attachment insecurity is associated with difficulties in adapting to cancer. Accumulating evidence points to the influence of avoidant emotion processes in this association. This study explored this pathway by examining the association between attachment insecurity and quality of life in women with breast cancer, and by exploring the mediating role of two avoidant emotion processes in this association. Women with breast cancer (N=155) completed measures of attachment, emotional suppression, emotional awareness, and quality of life. Avoidance of attachment was positively associated with emotional suppression (β= .29, p< .01) and lack of emotional awareness (β= .27, p < .01), and negatively associated with quality of life (β= -.22, p< .05). Lack of emotional awareness partially mediated the relationship between attachment avoidance and quality of life (indirect effect β= -.12, p= .008). Attachment anxiety was not associated with any variable. Attachment avoidance may hinder the process of adaptation to breast cancer and difficulties in identifying and describing emotions may be partly responsible for this influence. Access to and ability to benefit from social and medical supports is likely to depend on being able to engage with others and recognize and process emotions effectively. Research and clinical implications are discussed.